Efficient sustainable algorithm for numerical solutions of systems of fractional order differential equations by Haar wavelet collocation method - Thabet Abdeljawad; Rohul Amin; Kamal Shah; Qasem Al-Mdallal; Fahd Jarad (Alexandria Engineering Journal, 2020)
This manuscript deals a numerical technique based on Haar wavelet collocation which is developed for the approximate solution of some systems of linear and nonlinear fractional order differential equations (FODEs). Based on these techniques, we find the numerical solution to various systems of FODEs. We compare the obtain solution with the exact solution of the considered problems at integer orders. Also, we compute the maximum absolute error to demonstrate the efficiency and accuracy of the proposed method. For the illustration of our results we provide four test examples. The experimental rates of convergence for different number of collocation point is calculated which is approximately equal to 2. Fractional derivative is defined in the Caputo sense.